POST-COVID-19 HALAL TOURISM: A DESTINATION PERSPECTIVE IN EAST JAVA - Martaleni, Martaleni; Naser, M Jamal Abdul; Khoiriyah, Rizqiyatul; Hidayat, Noor (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
Almost all sectors of life in all countries have been affected by the Covid-19 pandemic. One sector that has been hit hard is the tourism industry. So that has forced tourism actors to design efficient marketing strategies to attract tourists. For this reason, tourism destination stakeholders are required to carry out creative strategies and expand market share by entering new segments in order to restore the increased demand for tourism products. In the tourism industry, halal tourism is a growing segment and has the potential to become an attractive new segment and market niche as the global Muslim population increases. Implementation of halal tourism requires efforts to build stakeholder awareness about the meaning and impact of halal tourism. Therefore, this study aims to provide an overview of the attributes of halal tourism that have been offered by existing tourist objects and future marketing strategies. Twentynine official websites of tourist destinations in East Java, Indonesia that offer halal tourism attributes were examined. Based on the results of data processing using a qualitative research approach it was concluded that tourist objects in East Java generally offer tourism products and services that meet the needs of Muslim tourists, but very few attributes of food and restaurants are certified and have a halal logo. For this reason, business awareness is needed with the support of stakeholders in order to brand business destinations that are friendly to Muslim tourists but can also be enjoyed by non-Muslim tourists.